Teenage Pregnancy and Its Outcome: A Scoping Review - Shalsabila, Dhea; Pamungkas, Ade Tia Bintang; Yuniasih, Dewi; Laariya, Tira Alfiani; Mawardi, Fitriana; Suprabandari, Suprabandari; Fauziyah Rahmawati, Nurul (Ahmad Dahlan Medical Journal, 2023)
Pregnant teenagers are deemed high risk and detrimental to motherhood and birth, as well as one of the world's major health issues, contributing to maternal and infant mortality and migration. Pregnancy Teenagers account for 11% of all births worldwide, with some large occurrences occurring in countries with intermediate income levels due to a variety of circumstances. Study The goal of this study is to learn about the effects of pregnancy on teenagers. Study This is a study scoping review that uses search tactics utilizing the keywords "teenage pregnancy, maternal, outcome, complications" in PubMed, Scopus, and other search databases for the time period 2018—2023. This study involves 19 publications with results risk maternal complications in pregnant teenagers like preeclampsia, eclampsia, anemia, postpartum hemorrhage, perineal tear, hyperthyroidism, oligohydramnios, infection channel urinary tract infection, condylomatosis, vaginal infection, HIV infection, infection syphilis, childbirth congestion, amniotic fluid broke premature birth, abortion, premature birth, and degree of maternal morbidity heavy. In newborns, outcomes included IUGR, low birth weight, preterm, needed bag valve mask resuscitation at birth, stillbirth, and neonatal mortality. Finally, pregnant teenagers have negative outcomes _ good for the mother or kid. That can become a vicious circle of negative consequences for health and the economy, so we must make an effort to reduce the impact of unfortunate pregnancies on youths.